Humanized care in orofacial harmonization: integrative literature review (Research, Society and Development, 2021)
Humanization has become a fundamental practice for the new profile of the dental surgeon. The patient is a complete being, who longs for technically capable professionals, and at the same time enjoy experiences based on the human aspect. Objective: To contribute to the discussion about the performance of the dental surgeon in the context of the HFOO, with emphasis on humanization. Methods: Methods: This is an integrative literature review, exploratory in nature, with a qualitative approach, according to Mendes (2008), which used the database: Scielo. For the development of the research, the descriptors were applied: "Dentistry", "Humanization", "Orofacial". Results: The numbers of aesthetic interventions in dentistry have been growing more and more. This search is linked to the desire to improve biopsychosocial well-being. To understand the growing search for orofacial harmonization, it is necessary to observe how dentistry has been treating the patient: going beyond what is standardized. Implicit in this approach are: listening, welcoming, clarifying, answering questions, and allowing the patient to participate in his/her treatment plan. Conclusion: It can be noted that humanization has been exalted as something essential in dentistry, due to the appreciation of the face and the smile in people's lives.